Structural regulation of a P2-type cathode via multi-cation doping for high-rate and stable sodium-ion batteries - Kang, Wenpei; Hu, Ying; Han, Mengjia; Fan, Xiaoyu; Sun, Daofeng (Journal of materials chemistry. A, Materials for energy and sustainability, 2025)
Mn, Ni-based P2-type layered Na 0.7 Mn 0.65 Ni 0.35 O 2 has been extensively studied because of its good air stability and electrochemical performance. However, it usually suffers from phase transitions at high voltage and different Na-vacancy ordering during sodium (de)intercalation, bringing about rapid capacity decline and poor rate capability. In this work, an entropy-modulation strategy based on multiple-cation doping is used to design a P2-type Na 0.7 Mn 0.65 Ni 0.15 Cu 0.12 Li 0.03 Fe 0.05 O 2 (NMNCLFO) cathode. Fe 3+ , Cu 2+ and Li + are successfully doped into the transition metal layers, which can synergistically regulate the lattice parameters, structure entropy and anionic redox activity, leading to improved structural stability and reaction kinetics. As a result, NMNCLFO has smoothed electrochemical curves, higher capacities (126.72 mA h g −1 at 50 mA g −1 ), and superior cycling stability (capacity retention of 76.2% at 1.0 A g −1 after 1000 cycles) and rate capability (76.2 mA h g −1 at 2.0 A g −1 ) compared with the undoped cathode and mono-cation doped cathodes. Based on the ex situ X-ray diffraction and in situ electrochemical impedance spectroscopy measurements, it is found that P2 NMNCLFO is stable during the (de)intercalation process, predicating that the regulated lattice parameters and lower Gibbs free energy are able to effectively inhibit the migration of transition metal (TM) ions and severe sliding of the TMO 2 layers.